Carminic Acid Linked to Silica Nanoparticles as Pigment/Antioxidant Bifunctional Excipient for Pharmaceutical Emulsions - Francisco Arriagada; Catalina Ugarte; Germán Günther; María Angélica Larraín; Víctor Guarnizo-Herrero; Santi Nonell; Javier Morales (MDPI AG, 2020)
The incorporation of pigments and natural polyphenols into inorganic matrices, resulting in a hybrid material that improves the resistance and chemical stability of the pigments and the antioxidant capacity of the materials, has been of great interest to the pharmaceutical, chemical and food industries. The aim of this work was to prepare and characterize a bifunctional pigment-antioxidant nanomaterial-based carminic acid-decorated solid core-mesoporous shell silica nanoparticles, evaluating its properties as a pigment, its antioxidant capacity and its properties as a chemical stabilizer of emulsions. The chemical stability of oil-in-water (O/W) Pickering emulsions was evaluated determining the stability of vitamin E solubilized in the oil phase. Carminic acid was attached through the action of coupling ethylcarbodiimide hydrochloride (EDC)/N-hydroxysuccinimide (NHS) agents, and the resulting spherical and homogeneous nanoparticles showed a diameter close to 175 nm. A notorious change of emulsion color was observed by the addition of the nanomaterial. Emulsions showed an attractive pink color, and when the pH was adjusted to pH 3 and pH 9, a change in color was observed, analogous to carminic acid in solution. The nanomaterial incorporation also improved chemical stability, decreasing vitamin E consumption to 9.26% of the initial value, demonstrating an important antioxidant effect of the developed nanomaterial.